South Koreans studying in DLSU-Manila: Challenges and opportunities in trade in education services - Suplico-Jeong, Luz (Animo Repository, 2013)
Trade in education services plays a crucial role in economies like Australia, Canada, New Zealand, UK, and USA. The largest component of trade in education services consists of students who travel abroad to study. This market is going to grow as international student mobility continues to increase. The Philippines has been a popular destination for South Korean students who want to study abroad because English is widely spoken. It offers the same quality of English education at a lower cost. This paper examines the economic contribution and challenges of the South Korean students in the Philippines. A marketing strategy to enhance this niche market includes promoting the Philippines as an ESL (English as a Second Language) destination toward the Korean families as families play crucial role in deciding which overseas schools to study. Further, this strategy should stress the Philippine advantage of having English education at a lower cost. © 2013 De La Salle University, Philippines.